2019
DOI: 10.4254/wjh.v11.i2.186
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis ofHFEgene in hereditary hemochromatosis and in diseases associated with acquired iron overload

Abstract: BACKGROUND Patients with hepatitis C virus (HCV) and hepatocellular carcinoma (HCC) may or not develop iron overload (IO), which is associated with worst prognosis, because can cause serious damage to organs. HFE gene controls the iron uptake from gut, particularly in patients with hereditary hemochromatosis (HH). AIM To identify associations between HFE coding region in patients exhibiting hereditary hemochromatosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In our study, carriers of two dominant alleles in H63D rs1799945 were less frequently diagnosed with hepatic iron overload ( Table 1 ). The role of HFE mutations in secondary iron overload diagnosed in CHC still remains unclear, as some studies show association H63D and C282Y mutations with elevated serum iron indices [ 19 , 29 ], liver iron deposits [ 11 ], and others reported no such relation [ 6 , 30 ]. Our results confirm the notion that HFE mutations may contribute to (but do not fully explain) hepatic iron accumulation in chronic hepatitis C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, carriers of two dominant alleles in H63D rs1799945 were less frequently diagnosed with hepatic iron overload ( Table 1 ). The role of HFE mutations in secondary iron overload diagnosed in CHC still remains unclear, as some studies show association H63D and C282Y mutations with elevated serum iron indices [ 19 , 29 ], liver iron deposits [ 11 ], and others reported no such relation [ 6 , 30 ]. Our results confirm the notion that HFE mutations may contribute to (but do not fully explain) hepatic iron accumulation in chronic hepatitis C.…”
Section: Discussionmentioning
confidence: 99%
“…The most common mutations, responsible for the majority of hemochromatosis cases in patients with East European ancestry, are mutations in the coding region of HFE gene: C282Y rs1800562, H63D rs1799945, and S65C rs1800730. The penetrance of these mutations is modulated by other genetic polymorphisms and unknown factors [ 6 ]. The rs855791 C > T mutation in TMPRSS6 gene encoding transmembrane serine protease matriptase-2, which cleaves multiple proteins from HFE and Bmp6 signaling pathways, reduces enzyme proteolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…This was suggested to have a contribution to the release of the cytokine, which triggers liver inflammation and fibrosis [94]. Other studies have focused on the role of the hemochromatosis gene (HFE) on the cellular level and have concluded that it promotes iron (Fe) overload in patients with HCV infection [96].…”
Section: Iron (Fe)mentioning
confidence: 99%